Eco-friendly accommodation facilities in Mladá Boleslav, Czechia: a case study - Scholz, Petr; Červová, Lenka (Turyzm/Tourism, 2021)
The purpose of this article is to evaluate the application of various green management measures in selected accommodation facilities in Czechia, namely in the town of Mladá Boleslav and its surroundings. This study was carried out using mixed research methods including semi-structured interviews with accommodation facility management staff. The interviews were complemented with a questionnaire survey which focused on the application of eco-friendly solutions in accommodation facilities. The total sample of participating facilities represented 39.6% of those in the town and its surroundings. In the data analysis stage, correspondence analysis was used. The results suggest that the higher the category, the stronger the trend to use eco-friendly methods in running accommodation facilities.